2018
DOI: 10.1016/j.scitotenv.2018.05.281
|View full text |Cite
|
Sign up to set email alerts
|

Wave farm effects on the coast: The alongshore position

Abstract: For wave energy to become a fully-fledged renewable and thus contribute to the much-needed decarbonisation of the energy mix, the effects of wave farms (arrays of wave energy converters) on coastal systems must be addressed. The objective of this work is to investigate the effects of wave farms on the longshore sediment transport and shoreline evolution of a gravel-dominated beach and, in particular, its sensitivity to the longshore position of the farm based on eight scenarios. Nearshore wave propagation patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Recent research on the impacts of a wave farm on the coastline has focused on the general layout of the farm [78] and its position alongshore [79]. There…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on the impacts of a wave farm on the coastline has focused on the general layout of the farm [78] and its position alongshore [79]. There…”
Section: Discussionmentioning
confidence: 99%
“…The selected wave farm case studies have the same number of WECs (11) and rows (2), but different spacings between WECs: D, 2D, 3D, and 4D (Figure 3), with D = 90 m [58]. The geometrical centres of the defined case studies are all located at the same position (Figure 1), which was found to be optimum from the standpoint of the wave power available to the WECs [31]; whereas the selected number of WECs and layout have been proved to be adequate for coastal protection purposes in recent years [43,58,78,79].…”
Section: Definition Of the Case Studiesmentioning
confidence: 99%
“…This especially concerns the collocation of the wave farms in the vicinity of the future wind projects, so that to benefit from important cost reductions related to the grid connection and to the operational expenditures (OPEX). Furthermore, an important additional argument in favor of marine energy farms is that they may play a significant role in coastal protection [25][26][27]. At this point, it has to be highlighted that the western side of the Black Sea is currently subjected to high erosion processes that need very expensive periodical investments.…”
Section: Discussionmentioning
confidence: 99%
“…Many coastal areas in the Black Sea are subjected to high erosion processes and the future nearshore farms can play an important role in the coastal protection, because they extract (or dissipate) part of the wave energy before the waves arriving to the shore [19][20][21][22][23][24]. Furthermore, this is a general problem for many coastal environments and the marine energy farms, besides providing electricity, can become an effective solution in the struggle against the coastal erosion [25][26][27].From this perspective, the present work has as a main objective to assess the most recent wave energy propagation patterns in the western side of the Black Sea. This considers also the fact that there is an obvious dynamics of the wave climate in the Black Sea having as a consequence important changes in the actual patterns of the nearshore wave propagation and inducing significant enhancements of the wave power.…”
mentioning
confidence: 99%
“…Since the wave energy sector is moving forward, the next step is to assemble various wave farms and test their operation. Therefore, it is important to predict in advance the expected coastal impact of such a project [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%